Mutation Hotspot for Changing the Substrate Specificity of β-N-Acetylhexosaminidase: A Library of GlcNAcases - Nekvasilová, Pavlína; Kulik, Natalia; Kotik, Michael; Petrásková, Lucie; Slámová, Kristýna; Křen, Vladimír; Bojarová, Pavla (International journal of molecular sciences, 2022)
β-N-Acetylhexosaminidase from Talaromyces flavus (TfHex; EC 3.2.1.52) is an exo-glycosidase with dual activity for cleaving N-acetylglucosamine (GlcNAc) and N-acetylgalactosamine (GalNAc) units from carbohydrates. By targeting a mutation hotspot of the active site residue Glu332, we prepared a library of ten mutant variants with their substrate specificity significantly shifted towards GlcNAcase activity. Suitable mutations were identified by in silico methods. We optimized a microtiter plate screening method in the yeast Pichia pastoris expression system, which is required for the correct folding of tetrameric fungal β-N-acetylhexosaminidases. While the wild-type TfHex is promiscuous with its GalNAcase/GlcNAcase activity ratio of 1.2, the best single mutant variant Glu332His featured an 8-fold increase in selectivity toward GlcNAc compared with the wild-type. Several prepared variants, in particular Glu332Thr TfHex, had significantly stronger transglycosylation capabilities than the wild-type, affording longer chitooligomers - they behaved like transglycosidases. This study demonstrates the potential of mutagenesis to alter the substrate specificity of glycosidases.
Keywords: β-N-acetylhexosaminidase; Acetylglucosamine; Talaromyces flavus; Acetylglucosaminidase; Substrate Specificity; Pichia pastoris; mutace; site-saturation mutagenesis; substrate specificity; beta-N-Acetylhexosaminidases; acetylglukosamin; beta-N-acetylhexosaminidasy; Kinetics; acetylglukosaminidasa; kinetika; substrátová specifita; site-directed mutagenesis; Mutation; acetylgalaktosamin; Acetylgalactosamine